HUBUNGAN PENGETAHUAN, STATUS EKONOMI, PERAN PETUGAS KESEHATAN DAN PERAN KELUARGA TERHADAP VAKSINASI HPV (HUMAN PAPILLOMA VIRUS) DI KLINIK DARA JINGGA KOTA JAMBI TAHUN 2017 - Nia Nurzia (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Abnormal cervical is still  in high levels of  which marked by the outbreak of the Human Papilloma Virus, It is not offset by the use of vaccination (HPV) Human Papilloma Virus which as the primary prevention of the spread of Human Papilloma Virus . recorded in Dara Jingga clinic in  2015, there were 226 people in the state of the cervix abnormal while those who making vaccination extremely low at only 40 people. Likewise, in 2016 there were 301 people in a state of abnormal cervical and vaccinated only 16 people . Based on it, this research is the research which aimed to determine the relationship between knowledge, economic status, family role and the role of health personnel  against the Human Papilloma Virus vaccination in Dara Jingga Clinic  Jambi City. This research is descriptive analytic with cross sectional design, the data collected through questionnaires, with a population was 321 people. using  acidental sampling technique with  sample was 32 people, research has been conducted on 22 to 24 August 2016 using univariate  and bivariate analysis assisted by a computer program. The results of the univariate analysis of vaccination picture were 10 respondents (31.3%) take advantage of HPV vaccination and 22 respondents (68,8%) did not take advantage of the HPV vaccination, an overview of knowledge were five respondents (15,6%) have sufficient knowledge, 15 respondents (46,9%) had a good knowledge,12 respondents (37,5%) had poor knowledge, an overview of economic status,  13 respondents (40,6%) had high economic status and  19 respondents (59,4% ) have lower economic status, description of the role of health workers13 respondents (40,6%) have a good role of health personnel and  19 respondents (59,4%) has the role of health personnel is not good. Overview of the role of the family, 11 respondents (34,4%) has the role of a good family and  21 respondents (65,6%) had a family roles goodles. the result of these studies show a relationship between the mother's knowledge by vaccination with HPV (Human Papilloma Virus ) with a p value of 0,035, the relationship between economic status with vaccination HPV (Human Papilloma Virus with p value 0,002, their relationship with the role of HPV vaccination of health workers with p value 0,002, their relationship with the family role of HPV vaccination with a p value of 0,004.Keywords: Knowledge, Economic Status, Role of health personnel, Role of Family,HPV Vaccination (Human Papilloma Virus)